El mundo de las mujeres en Joan Manuel Serrat - Alpízar Matamoros, Vilma (2016)
Joan Manuel Serrat is one of the greatest exponents of music in Spanish and Catalonian, and a clear example of the theory known as the butterfly effect, influencing several generations with the ideas presented in his songs and with the attitude assumed against in justice and intolerance. Through his view, there is a denunciation not only the role of women in a patriarchal society such as the one in the Franco's Spain and many others today, but also concerning the behavior that has been demanded from man in many areas to propose, in the end, a change towards a supportive society through education where principles like gender equality, respect towards diversity and equality prevail.